The challenges and opportunities clinical education in the context of psychological, educational and therapeutic dimensions in teaching hospital - Azizeh Barry; Azam Shahbaz (BMC Medical Education)
Abstract Background An appropriate clinical environment by providing learning opportunities, plays an important role in preparing students to apply the knowledge learned at the bedside. Since the lived experiences of patients in the clinical environment are effective on the quality of student’s learning, the present study was conducted with the aim of explaining the lived experiences of patients regarding bedside teaching. Materials and methods The present qualitative study was conducted using a content analysis approach in 2023 at the Imam Sajjad educational and therapeutic center affiliated with Tabriz Islamic Azad University of Medical Sciences. The studied samples were selected with purpose-based sampling among the patients admitted to this hospital (18 people). In addition, semi-structured interviews were used to collect data and Graneheim and Lundman’s approach for analysis of the data. Results From the analysis of participants’ narratives, 3 subcategories, and 17 primary concepts were obtained, which include the subcategory of the treatment dimension, the subcategory of the psychological dimension, and the next subcategory of education. Conclusion The results of the study showed that in the treatment dimension, the concerns of patients in bedside clinical education include an increase in the number and duration of visits, fear of students performing incorrect procedures, lack of recognition of the person responsible for treatment and accountability to different people, a feeling of prolonged hospitalization due to the education process, fear and anxiety of the unknown and unfamiliar terms expressed in clinical rounds, increased likelihood of infection due to a large number of students and their examination, less access to the relevant doctor due to academic busyness, and in the human ethical dimension, failure to maintain patient privacy and reporting the patient’s condition in public and examination by people of the same sex, lack of attention to the patient and his/her conversations during clinical rounds, and a greater focus on education. Lack of attention to the patient’s psychological and social issues and his/her hobbies and greater focus on his/her body, breach of trust, and mental and physical discomfort due to tests and examinations are more common, and in the education dimension, it includes helping to increase patient awareness and increasing patient alertness. Promoting self-care behaviors, increasing patient interest in learning about the disease, encouraging students to learn more, helping to establish communication between patients and healthcare providers, and helping to educate students.